Kedudukan Anak Kandung Non-Muslim dalam Menyelesaikan Hutang Almarhum Orang Tua Kandungnya yang Beragama Islam melalui Mediasi: Studi Putusan Perkara Nomor 5874/Pdt.G/2024/PA.Sby - Susilowati, Reny; Effendi, Prihatin; Suyanto, Suyanto (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study is grounded in the fact that, under Islamic law, death does not merely result in the transfer of property rights but also leaves legal obligations, particularly the settlement of debts, which must be fulfilled before the distribution of the estate. The issue becomes more complex when a biological child who is non-Muslim is involved in settling the debts of a deceased Muslim parent, especially through court-annexed mediation in the Religious Court. The central legal problem of this study lies in clarifying the boundary between the status of a faraidh heir and the capacity of a party who has a legal interest in resolving the deceased’s debts. This research aims to analyze the legal position of a non-Muslim biological child within the Islamic inheritance system, to explain that child’s position in the settlement of a Muslim decedent’s debts, and to examine the function of mediation in Case Number 5874/Pdt.G/2024/PA.Sby. The study employs normative legal research with a prescriptive-analytical character and a case-based library research design. The legal materials consist of primary, secondary, and tertiary legal sources, analyzed through statutory, case, conceptual, and Islamic normative approaches. The findings show that a non-Muslim biological child cannot be classified as a faraidh heir because religious difference constitutes a barrier to inheritance. However, such a child may be involved in debt settlement through civil legal capacity and a valid peace agreement. Thus, mediation does not alter inheritance status, but functions as a lawful mechanism for peaceful dispute resolution within the framework of Islamic law and Indonesian positive law